NUCLEATION AND ACCUMULATION OF GOLD IN YEAST CELLS - Korobushkina Ye.D.; Biryuzova V.I.; Korobushkin I.M.; Karavayko G.I. (My University, 1989)
When gold interacts under natural conditions with microorganisms, it is either concentrated, or dispersed. Our experiments have already shown that heterotrophic microorganisms can generate 'new' gold both on its original grain surfaces and in cells, and that much dissolved gold is reduced and occurs in the culture liquid as finely divided particles. However, the mechanism of gold crystallization in this process and the role of individual yeast-cell structures were neglected, so they are considered in this article. The work was done with a periodic culture of Candida utilis BKM Y-1668, grown on a synthetic medium. The mechanism generating gold crystals in cells may be represented as follows. After being dissolved by microorganisms, gold enters a cell and is localized in individual structures, forming crystallization nuclei for 'new' gold. This process proceeds most actively on membranes, glycogen and the cell wall. It eventually leads to coarsening of gold particles within cells. The gold there either migrates, or is freed after their lysis and precipitated in a different rock type. Thus, when biogeochemical barriers containing a large biomass of bacteria are created, gold may accumulate in its migration zone.